2018
DOI: 10.2337/cd17-0093
|View full text |Cite
|
Sign up to set email alerts
|

How Does Diabetes Affect Daily Life? A Beyond-A1C Perspective on Unmet Needs

Abstract: Given the progressive nature of type 2 diabetes, treatment intensification is usually necessary to maintain glycemic control. However, for a variety of reasons, treatment is often not intensified in a timely manner. The combined use of basal insulin and a glucagon-like peptide-1 receptor agonist is recognized to provide a complementary approach to the treatment of type 2 diabetes. This review evaluates the efficacy and safety of two co-formulation products, insulin degludec/liraglutide and insulin glargine/lix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 2 publications
0
16
0
Order By: Relevance
“…Beyond A1C, our results suggest OpenAPS improves the issues Gopisetty et al 21 found to most profoundly impact daily life for PWD: (1) time commitment and burden, (2) difficulty managing BG overall, and (3) hypoglycemia. Improvements in these three areas along with embedded safety features resulted in improvement to quality of life.…”
Section: Discussionmentioning
confidence: 61%
“…Beyond A1C, our results suggest OpenAPS improves the issues Gopisetty et al 21 found to most profoundly impact daily life for PWD: (1) time commitment and burden, (2) difficulty managing BG overall, and (3) hypoglycemia. Improvements in these three areas along with embedded safety features resulted in improvement to quality of life.…”
Section: Discussionmentioning
confidence: 61%
“…The jobs-to-be-done analysis is a widely used tool in market research to uncover and measure unmet needs. The survey included the following 15 outcomes that patients were least satisfied with from a list of 44 outcomes used in a previous dQ&A survey 18 : postprandial blood glucose <180 mg/dL; overnight blood glucose 70–130 mg/dL; blood glucose during the day 70–180 mg/dL; morning (fasting) blood glucose 70–180 mg/dL; HbA1c reduced or maintained at target; prevention of stress and anxiety caused by diabetes (“diabetes distress”); prevention of weight gain; prevention of hypoglycemic events not requiring medical assistance; prevention of severe hypoglycemic events requiring medical assistance; prevention of negative impact of diabetes on family and loved ones; general well-being throughout the day; simple and predictable diabetes management; reduced mental effort needed to manage diabetes; prevention of feelings of isolation and stigma due to diabetes; and flexibility with exercise and diet.…”
Section: Methodsmentioning
confidence: 99%
“…We've forgotten freedom means macro responsibility. Those disdaining masks cite their failure in prevention, ignoring their efficacy in containment (Godoy, 2020). People with disabilities, particularly those of us with chronic disabilities recognize the subtext of the unmasked: if you get the virus, that's your problem, not mine.…”
Section: A Country Of the Proudly Independentmentioning
confidence: 99%
“… 13. See “Unemployed Dad” (2020a) and Gopisetty et al (2018) for more on how insulin’s costliness has affected diabetics’ relationships and lives. …”
mentioning
confidence: 99%